Direct Regio- and Diastereoselective Diphosphonylation of Cyclic Enamines: One-Pot Synthesis of α,α′-Bis(diphenylphosphoryl)- and α,α′-Bis(diphenylphosphorothioyl)cycloalkanones - Jebli, Nejib; Debrouwer, Wouter; Berton, Jan K. E. T.; Van Hecke, Kristof; Stevens, Christian V.; Touil, Soufiane (Synlett, 2017)
A straightforward regio- and diastereoselective process has been developed for the synthesis of unprecedented symmetrical trans-α,α′-bis(diphenylphosphoryl)- and α,α′-bis(diphenylphosphorothioyl)-cycloalkanones, through the reaction of cyclic enamines with excess P-chlorodiphenylphosphine in the presence of triethylamine, followed by oxidation or sulfurization and hydrolytic workup.
Keywords: enamines; P-chlorodiphenylphosphine; α,α′-bis(diphenylphosphoryl)cycloalkanones; α,α′-bis(diphenylphosphorothioyl)cycloalkanones; P-ligands